﻿Update review: Etnopharmacological, bioactivity and phytochemical of Allium cepa L. - Sylvia Rizky Prima; Elfahmi; Elin Julianti; Irda Fidrianny (Pensoft Publishers, 2023)
Allium cepa L. is commonly used as a vegetable, spice, and in traditional medicine. In traditional medicine, A. cepa is applied based on its long-standing usage. This plant has been reported to have therapeutic effects on various conditions, including diabetes, various types of cancer, cough, influenza, dermatological problems, diarrhea, menstrual and abdominal pain, and malaria. Phytochemical analysis of A. cepa has identified polyphenols, flavonoids, steroid saponins, furostanol saponins, and sulfur compounds, which are believed to be responsible for its bioactivities. These bioactivities include antioxidant properties, which are associated with other activities such as anti-aging, antidiabetic, and anticancer effects. Additionally, A. cepa exhibits antimicrobial and antiplatelet activities.